Electronic properties of disclinations in carbon nanostructures - Sitenko, Yu.A.; Vlasii, N.D. (Вопросы атомной науки и техники, 2007)
The recent synthesis of strictly twodimensional atomic crystals (monolayers of carbon atoms) is promising a wealth of new phenomena and possible applications in technology and industry. Such materials are characterized by the Dirac-type spectrum of quasiparticle excitations, yielding a unique example of the truly twodimensional “relativistic” electronic system which, in the presence of disclinations, possesses rather unusual properties. We consider the influence of disclinations on densities of states and induced vacuum quantum numbers in graphene. Нещодавній синтез строго двовимірних атомних кристалів вуглецю обіцяє багато нових явищ та можливі застосування в технології і промисловості. Такі матеріали характеризуються спектром квазічастинкових збуджень діраківського типу, що дає унікальний приклад справді двовимірних «релятивістських» електронних систем, котрі при наявності дисклінацій мають досить незвичні властивості. Розглядається вплив дисклінацій на густини станів та індуковані вакуумні квантові числа графена. Недавний синтез строго двумерных атомных кристаллов углерода обещает изобилие новых явлений и возможные приложения в технологии и промышленности. Такие материалы характеризуются спектром квазичастичных возбуждений дираковского типа, что дает уникальный пример истинно двумерных «релятивистских» электронных систем, которые при наличии дисклинаций обладают достаточно необычными свойствами. Рассматривается влияние дисклинаций на плотности состояний и индуцированные вакуумные кванто вые числа графена.